“Making Sophisticated Lemonade out of Lemons”: Gender and Race in Organizing Everyday Culinary Practices - Rosa dos Santos Borsatto, Andiara; Fantinel, Leticia (Organizações & Sociedade, 2024)
This article aims to understand the organization of everyday life from the dynamics of gendering and racialization of cooking/eating practices engendered by ordinary managers. To do so, we problematize organization in a procedural and micropolitical ontology that allows to highlight how everyday cracks cross and give rise to practical rearticulations of a tactical and strategic nature. Narratives from ordinary black managers were captured and analyzed using the dialogic narrative technique, in the search for articulating the participating subjects’ voices with those of the authors of the text, the adopted theoretical framework and the readership. Our findings unveil the kitchen as a central organizational space for understanding these ordinary practices (although sometimes invisibilized and silenced), in heterogeneous processes of apprehension of culinary know-how, as well as in dynamic tactical and strategic articulations for survival purposes. Due to the moment in which the field research took place, the narratives describe these articulations amid the impacts caused by the covid-19 pandemic on the daily lives of the managers researched. Empirically, this study contributes by showing the heterogeneity in the organization of practices that constitute ordinary management, and which, in the context of a pandemic, produced narratives that differ from a hegemonic narrative of rupture, but which nevertheless impact on everyday life and give rise to reconfigurations. Theoretically, we contribute by showing how practices articulate apparently opposing repertoires such as private and public, sociability and business in everyday life. We have therefore advanced in understanding the organization of practices as constituents of ordinary management, in particular, from the crossings produced by the categories of race and gender that engender survival tactics and strategies.